Cell type-specific bipolar cell input to ganglion cells in the mouse retina. (1st March 2016) - Neumann, S.; Hüser, L.; Ondreka, K.; Auler, N.; Haverkamp, S.
Highlights: At least three types of ganglion cells stratify in S1 of the inner mouse retina. B-type ganglion cells show a denser dendritic arborization pattern than A-type cells. Both ganglion cell types receive 44% of their bipolar cell input from type 2 cells. JAM-B ganglion cells receive only 22% of their bipolar cell input from type 2 cells. Abstract: Many distinct ganglion cell types, which are the output elements of the retina, were found to encode for specific features of a visual scene such as contrast, color information or movement. The detailed composition of retinal circuits leading to this tuning of retinal ganglion cells, however, is apart from some prominent examples, largely unknown. Here we aimed to investigate if ganglion cell types in the mouse retina receive selective input from specific bipolar cell types or if they sample their synaptic input non-selectively from all bipolar cell types stratifying within their dendritic tree. To address this question we took an anatomical approach and immunolabeled retinae of two transgenic mouse lines (GFP-O and JAM-B) with markers for ribbon synapses and type 2 bipolar cells. We morphologically identified all green fluorescent protein (GFP)-expressing ganglion cell types, which co-stratified with type 2 bipolar cells and assessed the total number of bipolar input synapses and the proportion of synapses deriving from type 2 bipolar cells. Only JAM-B ganglion cells received synaptic input preferentially from bipolar cell types other than type 2 bipolar cells whereas the other analyzed ganglion cell types sampled their bipolar input most likely from all bipolar cell terminals within their dendritic arbor.